Asymmetric Effects of World Energy Prices on Inflation in Indonesia - Arintoko Arintoko; Lilis Siti Badriah; Dijan Rahajuni; Nunik Kadarwati; Rakhmat Priyono; Muhammad Amin Hasan (International Journal of Energy Economics and Policy, 2023)
This study analyzes the asymmetric effect of changes in world energy prices, which include crude oil, natural gas, and coal prices, and the exchange rate on consumer price index (CPI) inflation in Indonesia. The models used in the analysis are quantile regression and dynamic ordinary least squares. The period studied is monthly in the period 2001M01 - 2022M12. The study results show that world crude oil prices have asymmetrically positive effects on CPI inflation when world oil prices increase and decrease. The fall in the price of crude oil has a more significant effect than the increase. The asymmetric impact of world crude oil prices on CPI inflation was also found between lower and middle quantiles. However, the short-run impact of rising crude oil prices is only found in the 7th quartile. So, the long-run effect is more dominant than the short-run effect. The role of the fuel subsidy policy, which the government manages, is beneficial in reducing inflationary fluctuations originating from fluctuations in world crude oil prices. Efforts to develop oil refineries in Indonesia that need to be done to reduce imports of crude oil and fuel are expected to be able to reduce the impact of world oil price fluctuations on domestic inflation in the future.